Antioxidant Activity Of Tangerine (Citrus reticulata Blanco) So'e Extract As Traditional Tea - Tunmuni, Deglory; Astiti, Ni Putu Adriani; Sudirga, Sang Ketut (Metamorfosa: Journal of Biological Sciences, 2021)
The Citrus So'e plant is one of the leading community plants of the people of East Nusa Tenggara (NTT). The So'e tangerine is used as a raw material in the manufacture of orange juice and the peel has not been used. This research was conducted to utilize So'e tangerine peel as a traditional tea. The parameters observed included the active compound group, antioxidant activity, the type of active compound for So'e tangerine peel and the public's perception of the traditional So'e tangerine peel tea. The research method was carried out by qualitative phytochemical tests, test for the content of flavonoids, phenolics, and tannins by spectaphotometry, antioxidant tests using the DPPH method, testing for the types of active compounds using GC-MS and organoleptic tests to determine the level of consumer preference. The results showed that So'e tangerine peel extract had active compounds, namely flavonoids, phenolics, tannins, steroids, triterpenoids and alkaloids and So'e tangerine peel extract contained flavonoids = 253.901 mg / 100g QE, phenolic = 61.6099 mg / 100g GAE, tannin = 60.0496 mg / 100g TAE which has the potential as an antioxidant with an IC50 value of 81.811 mg / L which is included in the strong antioxidant category, and has various types of active compounds, namely the nonpolar fraction contains 53 compounds and the polar fraction contains 46 compounds activity and the level of public preference for So'e tangerine peel tea was higher in refined tea than coarse tea.  Keywords: Citrus reticulata , phytochemicals, DPPH, GC-MS, traditional tea.